Beyond the surface: A case study about nevus sebaceous removal for cosmetic concerns - Joshua Lewis; Jatinder P Singh; Ernst J Nicanord (SAGE Open Medical Case Reports)
Nevus sebaceous, a benign scalp birthmark, typically presents without immediate health concerns but may require removal as it becomes bothersome with age. Symptoms are typically cosmetic, lacking pain or bleeding. Clinical presentation varies with age, initially appearing as a smooth, hairless yellowish patch, later evolving into an elevated lesion after the onset of puberty. We report a case of a 25-year-old female with nevus sebaceous. Despite its benign nature, the patient opted for excision due to cosmetic concerns and the potential for malignancy. Surgical removal was successful without complications. This case underscores the importance of early diagnosis and intervention to alleviate discomfort and potential malignancy. While rare, malignant transformation can occur, emphasizing the need for vigilant monitoring and timely surgical intervention, particularly during pre-puberty stages. Treatment should prioritize removal to prevent malignant progression and address cosmetic concerns. Further research is needed to refine management strategies for nevus sebaceous.